Bacteria‐driven production of alkyl nitrates in seawater. Issue 2 (23rd January 2015) - Kim, Michelle J.; Michaud, Jennifer M.; Williams, Renee; Sherwood, Byron Pedler; Pomeroy, Robert; Azam, Farooq; Burkart, Michael; Bertram, Timothy H.
Abstract: Aircraft‐ and ship‐borne measurements have shown that the ocean is a large, diffuse source for short chain (C1 –C3 ) gas phase alkyl nitrates (RONO2 ). Photochemical production of RONO2 has been demonstrated previously as a viable mechanism in surface waters; however, it cannot account for the observed depth profile of RONO2, suggesting an additional, dark RONO2 production mechanism. We present measurements of gas phase C1 –C5 alkyl nitrates emitted from seawater in a controlled mesocosm experiment conducted under low‐light conditions in a glass‐walled wave channel. Ethyl and butyl nitrate emission rates from seawater are strongly correlated with the abundance of heterotrophic bacteria ( R 2 ≥ 0.89) and show no correlation to chlorophyll a concentration. Controlled flask experiments conducted using ambient and sterile seawater, inoculated with a heterotrophic bacterium, confirm that bacterial driven production of select RONO2 can proceed efficiently in the absence of light. Key Points: Trace gas emissions from a controlled mesocosm experiment Estimates of biotic oceanic alkyl nitrate production rates Bacteria‐driven production of short chain alkyl nitrates